2012
DOI: 10.2310/7290.2012.00011
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunogenicity of Novel Gene Immunogens in Mice Monitored by in Vivo Imaging

Abstract: The efficient cell-mediated immune response clears cells expressing deoxyribonucleic acid (DNA) immunogens, but there are no methods to monitor this in vivo. We hypothesized that immune-mediated clearance can be monitored in vivo if DNA immunogens are coexpressed with reporter(s). To test this, we designed genes encoding human immunodeficiency virus 1 (HIV-1) reverse transcriptase (RT) fused via its N- or C-terminus to 30-amino acid-long Gly-Ala-repeat of Epstein-Barr virus nuclear antigen 1 or via the N-termi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 66 publications
(127 reference statements)
1
16
0
Order By: Relevance
“…We have earlier shown that diminishment of bioluminescence induced by the expression of reporter gene coinjected with DNA immunogen correlates with the induction of polyfunctional cellular responses against the immunogen [8, 47] specifically with IFN- γ /Il-2 responses of CD4 T cells [8]. To monitor this effect, mice were coinjected with RT gene variants and a reporter gene encoding firefly luciferase (Luc) and assessed for the levels of bioluminescence on days 1, 3, 6, 9, 15, and 22 postimmunization.…”
Section: Resultsmentioning
confidence: 99%
“…We have earlier shown that diminishment of bioluminescence induced by the expression of reporter gene coinjected with DNA immunogen correlates with the induction of polyfunctional cellular responses against the immunogen [8, 47] specifically with IFN- γ /Il-2 responses of CD4 T cells [8]. To monitor this effect, mice were coinjected with RT gene variants and a reporter gene encoding firefly luciferase (Luc) and assessed for the levels of bioluminescence on days 1, 3, 6, 9, 15, and 22 postimmunization.…”
Section: Resultsmentioning
confidence: 99%
“…This was done by assessing the level of expression in the injection sites of the reporter gene of firefly luciferase, co-delivered with the IN gene variants [83]. As we have recently shown, co-injection of Luc reporter gene with a potent gene immunogen results in a rapid loss of the in vivo reporter activity (decrease of bioluminescence) [83]. Here, co-delivery of Luc and IN genes led to a significant, 10- to 15-fold decrease in the total photon flux from the site of immunization three weeks post immunization.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] With this in mind, we have undertaken a study of the oxidative stress and oxidative stress response on a panel of HIV-1 reverse transcriptase (RT) genes of high to low immunogenicity. [34][35][36] All RT genes were found to induce oxidative stress in the transfected human embryonic kidney cells. The capacity of an RT gene to induce ROS correlated with its capacity to induce RT-specific IFN-γ responses in mice.…”
Section: Introductionmentioning
confidence: 99%